ANALISIS KETAHANAN KOMBINASI TEKNIK KRIPTOGRAFI RAIL FENCE DAN VIGENERE CIPHER TERHADAP SERANGAN BRUTE-FORCE MENGGUNAKAN PEMROGRAMAN PYTHON: Algorithms, Kriptografi, Rail Fence cipher, Vigenere cipher, Brute-Force - Rachmawati, Aulia; Anzari, Yandi; Fatih, Muhammad Damas; Pariyadi, Pariyadi (LP2M Universitas Nurdin Hamzah, 2025)
Data is an essential asset that must be protected due to its strategic role in maintaining the continuity of information systems. Therefore, data security becomes a crucial aspect in information management. One of the approaches to ensure data security is through the application of cryptographic techniques. Two commonly used classical cryptographic algorithms are the Rail Fence Cipher and the Vigenere Cipher. However, the use of a single algorithm has weaknesses, as it remains vulnerable to brute-force attacks. This study aims to combine two cryptographic methods, namely the transposition technique (Rail Fence) and the substitution technique (Vigenere), to enhance resistance against brute force attacks. The research employs an experimental method by implementing the combined algorithms using the Python programming language. Testing was conducted on three scenarios: encryption using Rail Fence, Vigenere, and their combination. The results show that the combined algorithm increases key space and produces more complex character distribution patterns, thereby improving security against brute-force attacks.